The influence of the e-samsat program, quality of tax officer services, taxation socialization, and moral obligations on taxpayer compliance in paying motor vehicle taxes - Rifka Kusuma Ardani; Kurniawati, Lintang (Institute of Accounting Research and Novation (IARN), 2024)
This research seeks to analyze how the e-Samsat program, the quality of tax officer services, tax socialization, and moral obligations influence taxpayer compliance in paying motor vehicle taxes at the Samsat Office in Wonogiri Regency. A quantitative approach is utilized, employing multiple linear regression. The study’s dependent variable is taxpayer compliance, with independent variables including e-Samsat, service quality, tax socialization, and moral obligations. The sampling method applied is purposive sampling, focusing on specific criteria for motor vehicle taxpayers in Wonogiri Regency. The findings indicate that the e-Samsat program does not significantly impact taxpayer compliance, while both service quality and tax socialization show a significant influence. Moral obligations, however, are not found to have a significant effect on taxpayer compliance.